2022
DOI: 10.1002/micr.30891
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome after transfer of brachialis on anterior interosseous and supinator on posterior interosseous nerves: A preliminary report

Abstract: Objective Traumatic spinal cord injury (SCI) resulting in tetraplegia is a leading cause of morbidity among young adults worldwide and its management remains challenging. Restoring hand function in these patients must be considered a top priority with great impact on their quality of life (QOL); although nerve and tendon transfer have been extensively described, type of procedure to be chosen is not standardized and few studies have determined the functional outcome of those procedure and their impact on QOL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…There are few reports on outcomes of nerve transfers for SCI. [5][6][7][8][9] Existing reports convey that the SUP-PIN transfer has been found to be generally more reliable than nerve transfers for elbow extension and finger flexion and that only antigravity strength is required for functionality. Bertelli's series found that 12/13 transfers achieved antigravity strength.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are few reports on outcomes of nerve transfers for SCI. [5][6][7][8][9] Existing reports convey that the SUP-PIN transfer has been found to be generally more reliable than nerve transfers for elbow extension and finger flexion and that only antigravity strength is required for functionality. Bertelli's series found that 12/13 transfers achieved antigravity strength.…”
Section: Discussionmentioning
confidence: 99%
“…8 Another found that 50% achieved (an average of) M3 in the EDC and 43% M3 for thumb extension. 9 We report the MRC for every digit as we felt taking the strongest digit value does not fully represent the extent of hand opening and failing digits could adversely affect function and require additional procedures (eg, side-to-side tenodesis). Typically, though, we found the distribution of EDC strength to be relatively uniform.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Graded Redefined Assessment of Strength, Sensibility and Prehension (GRASSP) Test is a valid and reliable test that was designed to measure functional outcomes in complete and incomplete cervical SCI [45] . The GRASSP has been shown to be predictive of overall UE and self-care function [49] and was used in 1/26 studies [50] . GRT was originally developed to assess outcomes after neuroprosthesis implantation in people with SCI [46] .…”
Section: Functional Outcomesmentioning
confidence: 99%